INFLUENCE OF COW SKIN CLEANING ON PHYSIOLOGICAL PARAMETERS UNDER HEAT STRESSES IN WARM SEASON - Ivanov Yuri Grigorievich; Baimukanov Dastanbek Asylbekovich; Borulko Vyacheslav Grigorievich; Ponizovkin Dmitry Andreevich; Dzhanabekova Gulmira Kumiskalievna (Scientific Journal of Pedagogy and Economics, 2020)
The results of the research on reducing heat stress in cows arising at temperatures above 25 °C by enhancing the intensity of heat transfer between animal and environment in the warm season by reducing skin contamination with various cleaning methods are considered. The article presents analytical expressions that establish the dependence of the influence of environmental parameters on the heat transfer of an animal. Analytical expressions connect the clinical and physiological parameters of animals: skin temperature, heart rate, respiration rate with environmental parameters: temperature, relative humidity, and air flow rate; the expressions also take into account the condition of the skin and cleaning methods. The study hypothesizes that after cleansing the skin of animals during the warm and hot season, the intensity of heat transfer between the animal and the environment will increase from pollution, which will allow the animal to more effectively remove excess heat from the body. The research methodology is based on the determination of the clinical and physiological parameters of animals with various methods of cleaning the skin: skin temperature, respiratory rate, and heart rate of animals. The studies have shown that the respiratory rate in animals after dry cleaning is less by 6.08% than in animals that did not receive skin cleansing. With wet cleaning, the difference is 9.63%; the heart rate in animals after dry cleaning is less by 4.45% than in animals that have not received cleansing of the skin. With wet cleaning, the difference is 12.95%; as a result of wet cleaning, the skin area has a temperature lower on average by 11.85% than the untreated skin area, whereas after dry cleaning the difference is 2.51%. The results suggest that the use of wet cleaning of cow skin in the warm season is more effective than dry cleaning.